Ti3C2Tx as an Advanced Support Material for Polymer Electrolyte Fuel Cell Catalysts to Facilitate the Oxygen Reduction Reaction - America, Tyler Daniel (Department of Chemical Engineering, 2023)
Polymer electrolyte fuel cell's (PEFC's) have the potential to offer a leading energy conversion technology. These fuel cells make use of hydrogen and oxygen and by means of a chemical reaction, electricity, heat and liquid water are produced. In 2015 the Department of Energy (DoE) of the United States declared a 5000-hour lifetime target for transport applicable fuel cells. With current technological limitation, the achieved lifespan is, however, restricted to only 1700-hours. An assessment to find a more active but primarily more durable support for the oxygen reduction reaction (ORR) in a PEFC than the currently employed carbonaceous support was therefore undertaken. A MXene, Ti3AlC2 was selected for assessment based on its theoretically suitable electrical and thermal conductivities, as well as its possession of among the strongest resistance to oxidation of the many different MAX phases. The synthesis of high (>50 m2 g -1 ), specific surface area, delaminated Ti3C2Tx flakes was attempted first with mild in-situ HF conditions. While this method could both etch and delaminate flakes in a single stage, because the flake size remained large and unchanged, the specific surface area was not seen to increase to the outlined requirements. To synthesize Ti3C2Tx flakes with a high specific surface area, HF etching was therefore employed. In this report, 0.5 g of 400-mesh Ti3AlC2 flakes synthesized by hot pressing were etched in 10 ml of 48 wt % HF for 24 hours at 30 °C. After micronizing for 10 minutes and probe sonicating in solution for a further 40 minutes, high specific surface area (86 m2 g -1 ), delaminated Ti3C2Tx flakes were attained. Using metal organic chemical deposition, well dispersed 2- 5 nm platinum particles were successfully deposited onto the support material. Initial electrochemical performance evaluations indicated a lack of conductivity which restricted electron transport and therefore limited catalyst activity. This was determined to be the result of more defective flakes and by correlation, an increase in interfaces leading to increased resistance. With the incorporation of carbon to the catalyst material to synthesize a hybrid electrode, a positive result confirming ORR activity was attained. While the electrochemical surface area (ECAS) was less than half of that of Pt/C (80 vs 28 m2 g -1 ), it confirmed where the synthesis constraints lie. In review of the durability results, it was found that trapped intermediates between high specific surface area MXene sheets not only restricts access to catalytic sites but are further protonated and reduced to form hydrogen peroxide which causes irreversible damage the PEFC's catalyst membrane.